Application of System-Dynamic Modeling to Improve Distribution Logistics Processes in the Supply Chain - Galimkair Mutanov; Sayabek Ziyadin; Askhat Serikbekuly (Communications - Scientific letters of the University of Zilina, 2020)
This article presents an approach of improve logistics processes with the system dynamics modeling of two different processes scenarios. System dynamics is used, not only as a causal loop diagram, but calculated measures of end-user satisfaction indicators were provided by experts, as well. Literature review of fundamental definitions and recent ideas in subject of supply chain management (SCM), system dynamics (SD), business processes model and notation (BPMN) and distribution logistics for dozens of major sources, has been made. In the work, methods of expert interviews, content analysis of recent publications, system-dynamic modeling and business process modeling, were used. Developed BPMN-models of distribution logistics business processes are given in Appendices #1 and #2.